2012
DOI: 10.4028/www.scientific.net/amr.550-553.1400
|View full text |Cite
|
Sign up to set email alerts
|

Feather Degradation and Keratinase Production by <i>Stenotrophomonas maltophilia</i> DHHJ

Abstract: Feathers, as a waste, are produced in large quantities from poultry processing industry every year. In this paper, feathers were biodegraded by Stenotrophomonas maltophilia DHHJ which was isolated from soil samples. The results show that the optimal conditions for the feather degradation and the keratinase production are 2.5% feather as substrate, the initial pH of 7.8 and cultivation at 40 °C for 5 days. Salts, KCl and NaCl, can increase feather degradation slightly. The proper concentration of Tween 80 can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, neutral to weakly alkaline pH was more suitable for bacteria including B. tropicus Gxun-17 to produce keratinase [ 34 – 36 ]. Some reports have shown that the keratinase activity of B. licheniformis ALW1 reached 72.2 U/mL, that of B. zhangzhou reached 49.96 U/mL and that of S. maltophilia DHHJ reached 10.0 U/mL by optimising fermentation conditions and fermentation medium [ 8 , 10 , 11 ]. After optimisation, the keratinase activity of B. tropicus Gxun-17 in this study reached 112.57 U/mL, which was 3.18-fold higher than the activity of basic medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, neutral to weakly alkaline pH was more suitable for bacteria including B. tropicus Gxun-17 to produce keratinase [ 34 – 36 ]. Some reports have shown that the keratinase activity of B. licheniformis ALW1 reached 72.2 U/mL, that of B. zhangzhou reached 49.96 U/mL and that of S. maltophilia DHHJ reached 10.0 U/mL by optimising fermentation conditions and fermentation medium [ 8 , 10 , 11 ]. After optimisation, the keratinase activity of B. tropicus Gxun-17 in this study reached 112.57 U/mL, which was 3.18-fold higher than the activity of basic medium.…”
Section: Discussionmentioning
confidence: 99%
“…LM19 after the optimisation of conditions [ 9 ]. After optimisation, keratinase activity of Stenotrophomonas maltophilia DHHJ reached 10.0 U/mL [ 10 ].…”
Section: Introductionmentioning
confidence: 99%